Total Mesorectal Excision vs. Transanal Endoscopic Microsurgery Followed by Radiotherapy for T2N0M0 Distal Rectal Cancer: A Multicenter Randomized Trial - Tang, Junwei; Zhang, Yue; Zhang, Dongsheng; Zhang, Chuan; Jin, Kangpeng; Ji, Dongjian; Peng, Wen; Feng, Yifei; Sun, Yueming (Frontiers in Surgery, 2022)
Introduction Transanal Local excision (TLE) is an organ-preserving treatment alternative for patients with early rectal cancer. However, TLE alone is associated with greater risk of local recurrence and inferior survival in comparison with total meso-rectal excision (TME). As an important adjuvant therapy, radiotherapy can effectively reduce the local recurrence rate of rectal cancer. This study aimed to investigate whether TLE followed by radiotherapy can be a valid alternative to TME in T2N0M0 distal rectal cancer treatment. Methods We plan to recruit 168 participants meeting established inclusion criteria. Following informed consent, participants will randomly receive treatment protocols of TLE followed by radiotherapy (a total dose of 45-50.4 Gy given in 25-28 factions) or TME. Depending on postoperative pathology, the participants will receive either long-term follow-up or further treatment. The primary endpoint of this trial is 3-year local recurrence rate. The secondary end points include 3-year disease-free survival rate, 3-year overall survival rate, 3-year mortality rate, postoperative quality of life, postoperative safety index, intraoperative evaluation index and postoperative short-term evaluation index. Discussion This trial is the first prospective randomized trial to investigate the rectum preserving treatment by using transanal endoscopic mcrosurgery followed by radiotherapy. Clinical Trial Registration The trial has been registered on Clinicaltrials.gov (NCT04098471).